1982
DOI: 10.2118/8924-pa
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Potential of the New Albany Shale Group (Devonian-Mississippian) in Southeastern Illinois

Abstract: Data from geologic and geochemical studies of the New Albany shale group indicate that a 19-county area of southeastern Illinois is a favorable area to explore for gas in Devonian shale. Although gas shows in the shales have been encountered in several wells drilled in this area, no attempts were made to complete or evaluate a shale gas well until 1979. In 1979, core samples from two Wayne County wells were obtained, permitting the first quantitative assessment of gas content of the shales in this area. Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The mechanism of CH 4 adsorption in organic matters has been well documented, illustrating that the surface functional groups and micropores provided the adsorption sites for CH 4 (Loucks et al, 2009;Ross and Bustin, 2007Zhang et al, 2012). The effects of the characteristics of organic matters on CH 4 adsorption, including the total organic carbon (TOC) content (Cluff and Dickerson, 1982;Harris et al, 1970), kerogen type (Zhang et al, 2012) and thermal maturity (Loucks et al, 2009), have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of CH 4 adsorption in organic matters has been well documented, illustrating that the surface functional groups and micropores provided the adsorption sites for CH 4 (Loucks et al, 2009;Ross and Bustin, 2007Zhang et al, 2012). The effects of the characteristics of organic matters on CH 4 adsorption, including the total organic carbon (TOC) content (Cluff and Dickerson, 1982;Harris et al, 1970), kerogen type (Zhang et al, 2012) and thermal maturity (Loucks et al, 2009), have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, shale gas has provided substantive economic benefits in the United States (Curtis, 2002;Jarvie et al, 2007) and has inspired intensive research activity worldwide. Studies undertaken in the United States have identified total organic carbon (TOC) content, maturity, mineralogical composition, porosity, permeability, and thickness as key parameters in assessments of shale gas resources (Harris et al, 1978;Cluff and Dickerson, 1982;Pollastro et al, 2003;Montgomery et al, 2005). Moreover, the methods used to measure porosity and pore structure have received considerable attention, as these parameters are important in the evaluation of shale gas reserves Bustin, 2008, 2009;Loucks et al, 2009Loucks et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Studies undertaken in the United States identify total organic carbon content (TOC), maturity, mineral matter, porosity, permeability and thickness as the key parameters in assessment of gas shale resources (Harris et al, 1978;Cluff and Dickerson, 1982;Pollastro et al, 2003;Montgomery et al, 2005). However, due to the heterogeneity of shale gas reservoirs, relationships established for particular shales cannot be applied elsewhere.…”
Section: Introductionmentioning
confidence: 99%